Voltage-Gated Nanoparticle Transport and Collisions in Attoliter-Volume Nanopore Electrode Arrays - Fu, Kaiyu (Small, 2018)
Single nanoparticle analysis can reveal how particle-to-particle heterogeneity affects ensemble properties derived from traditional bulk measurements. High-bandwidth, low noise electrochemical measurements are needed to examine the fast heterogeneous electron-transfer behavior of single nanoparticles with sufficient fidelity to resolve the behavior of individual nanoparticles. Herein, nanopore electrode arrays (NEAs) are fabricated in which each pore supports two vertically spaced, individually addressable electrodes. The top ring electrode serves as a particle gate to control the transport of silver nanoparticles (AgNPs) within individual attoliter volume NEAs nanopores, as shown by redox collisions of AgNPs collisions at the bottom disk electrode. The AgNP-nanoporeis system has wide-ranging technological applications as well as fundamental interest, since the transport of AgNPs within the NEA mimics the transport of ions through cell membranes via voltage-gated ion channels. A voltage threshold is observed above which AgNPs are able to access the bottom electrode of the NEAs, i.e., a minimum potential at the gate electrode is required to switch between few and many observed collision events on the collector electrode. It is further shown that this threshold voltage is strongly dependent on the applied voltage at both electrodes as well as the size of AgNPs, as shown both experimentally and through finite-element modeling. Overall, this study provides a precise method of monitoring nanoparticle transport and in situ redox reactions within nanoconfined spaces at the single particle level.